Instrumentos de avaliação da aprendizagem matemática: contribuições e convergências de uma revisão integrativa - FREITAS, Claúdio Lopes de (Universidade Federal de Ouro Preto, 2022)
Text inventories debate about instruments to assess mathematics learning in articles published in the journal “Educação Matemática em Revista”, by the Brazilian Society of Mathematics Education. Research methodology consists of an integrative review, with a sample of 24 articles, published from 1993 to 2021. Results indicate the proposition of a dialogic and formative assessment in mathematics. Furthermore, the studies converge about the procedural nature of assessment and its articulation with different languages, as well as the need to diversify assessment instruments, including creatively reconfiguring those of a summative character, such as the test.